Analysis of Students' Needs for Guidance and Counseling Services in Higher Education in Overcoming Students' Mental Well-Being: A Systematic Literature Review - Lena Marianti; Sudarwan Danim; Nurul Astuti Yensy (KURAS Institute, 2025)
This research aims to analyze students' needs for guidance and counseling (BK) services in higher education in order to improve students' mental well-being. The research method used is Systematic Literature Review (SLR), by examining eight relevant scientific articles published between 2020 and 2025. Data sources were obtained through the ScienceDirect, ResearchGate, SpringerLink, and Google Scholar databases, using the keywords